2012
DOI: 10.5606/tjr.2012.006
|View full text |Cite
|
Sign up to set email alerts
|

Using Clinical and Multislice Computer Tomographic Features to Assess Temporomandibular Joint Osseous Involvement in Rheumatoid Arthritis: A Preliminary Study

Abstract: Amaç: Bu çalışmada, romatoid artrit (RA) hastalarında çok kesitli bilgisayarlı tomografi (ÇKBT) taraması ve multiplanar rekonstrüksiyon (MPR) ile temporomandibüler eklemin (TME) osseöz tutulumu değerlendirildi ve klinik, laboratuvar ve radyolojik hastalık parametreleri açısından bir ilişki olup olmadığı araştırıldı. Hastalar ve yöntemler:Çalışmaya kesin RA tanısı konmuş 24 kadın hasta (ort. yaş 35.5±6.6 yıl; dağılım 38.3-42 yıl) dahil edildi. Değerlendirme tıbbi öykü, fizik muayene ve klinik araştırma ile gerç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 32 publications
4
11
2
Order By: Relevance
“…Osteophytes were detected in the RA group with a frequency of 32.1%. This is in accordance with Gheita et al, 14 who detected osteophytes in 33.33% of the patients they studied. A lower frequency (10%) was detected by Voog et al 16 …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Osteophytes were detected in the RA group with a frequency of 32.1%. This is in accordance with Gheita et al, 14 who detected osteophytes in 33.33% of the patients they studied. A lower frequency (10%) was detected by Voog et al 16 …”
Section: Discussionsupporting
confidence: 93%
“…2 4 In this study, RF was positive in 64.3% of the patients. This agrees with the results of Gheita et al, 14 Kurup et al, 29 and Yilmaz et al, 1 who found RF positivity in 75%, 67%, and 60.71% of cases, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations